Patterns and Interpretation of Tafsir Science - Mochamad Imamudin (STAI Miftahul Ula Nganjuk, 2019)
The Qur'an is the revelation of God with the absolute truth that is the source of Islamic teachings. The Qur'an is a holy book for Muslims who give clues to the right path. It serves to provide welfare and happiness for people, both personally and in groups. He was also a place of grievances and outpouring of hearts for those who read it. The Qur'an is like an ocean that never dries its water, its waves never subsides, the riches and treasures that it contains never run out, can be crossed and interrown in various ways, and provide tremendous benefits and impacts for life Human. In his position as Scripture and miracles for the Muslims, the Qur'an is a source of security, motivation, and inspiration, the source of all legal resources that are never dry for the one who imfew it. It contains historical documents that record socio-economic, religious, ideological, political, and cultural conditions of human civilization until the VII-century AD. If that is the case, then the understanding of the verses of the Qur'an through interpretation, having a very large role for the development of the people, guarantees the key term to open the warehouse of the Simsimpani that is buried in the Qur'an. As a living guideline for all ages, and in many aspects of human life, the Qur'an is an open ended scripture to understand, interpret and be offered in the perspective of the interpretation method and the perspective of the dimensions Human life. From here there came the sciences to study the Qur'an from various aspects, including the science of interpretation. This paper will discuss about the science of Tafsir covering its history and development, as well as patterns and methods in interpretation.